Growth of non‐English‐language literature on biodiversity conservation. Issue 4 (24th March 2022) - Chowdhury, Shawan; Gonzalez, Kristofer; Aytekin, M. Çisel Kemahlı; Baek, Seung‐Yun; Bełcik, Michał; Bertolino, Sandro; Duijns, Sjoerd; Han, Yuqing; Jantke, Kerstin; Katayose, Ryosuke; Lin, Mu‐Ming; Nourani, Elham; et al.
Abstract: English is widely recognized as the language of science, and English‐language publications (ELPs) are rapidly increasing. It is often assumed that the number of non‐ELPs is decreasing. This assumption contributes to the underuse of non‐ELPs in conservation science, practice, and policy, especially at the international level. However, the number of conservation articles published in different languages is poorly documented. Using local and international search systems, we searched for scientific articles on biodiversity conservation published from 1980 to 2018 in English and 15 non‐English languages. We compared the growth rate in publications across languages. In 12 of the 15 non‐English languages, published conservation articles significantly increased every year over the past 39 years, at a rate similar to English‐language articles. The other three languages showed contrasting results, depending on the search system. Since the 1990s, conservation science articles in most languages increased exponentially. The variation in the number of non‐English‐language articles identified among the search systems differed markedly (e.g., for simplified Chinese, 11, 148 articles returned with local search system and 803 with Scopus). Google Scholar and local literature search systems returned the most articles for 11 and 4 non‐English languages, respectively. However, the proportion of peer‐reviewed conservation articles published in non‐English languages was highest in Scopus, followed by Web of Science and local search systems, and lowest in Google Scholar. About 20% of the sampled non‐English‐language articles provided no title or abstract in English; thus, in theory, they were undiscoverable with English keywords. Possible reasons for this include language barriers and the need to disseminate research in countries where English is not widely spoken. Given the known biases in statistical methods and study characteristics between English‐ and non‐English‐language studies, non‐English‐language articles will continue to play an important role in improving the understanding of biodiversity and its conservation. Resumen: Resumen : El inglés es reconocido como el idioma de la ciencia y las publicaciones en inglés (PI) cada vez son más. Con frecuencia se asume que el número de publicaciones en idiomas diferentes al inglés está disminuyendo. Esta suposición contribuye al uso reducido de las publicaciones que no están en inglés en las ciencias, prácticas y políticas de la conservación, especialmente a nivel internacional. Sin embargo, el número de artículos de conservación publicados en diferentes idiomas está muy mal documentado. Usamos sistemas de búsqueda locales e internacionales para buscar artículos científicos sobre la conservación de la biodiversidad publicados entre 1980 y 2018 en inglés y en quince idiomas diferentes al inglés. También comparamos la tasa de incremento de publicaciones en los diferentes idiomas. En doce de los quince idiomas diferentes al inglés, los artículos de conservación publicados incrementaron significativamente cada año durante los últimos 39 años, una tasa similar a los artículos en inglés. Los otros tres idiomas mostraron resultados contrastantes según el sistema de búsqueda. Desde la década de 1990, los artículos sobre ciencias de la conservación incrementaron exponencialmente en la mayoría de los idiomas. La variación en el número de artículos identificados en idiomas diferentes al inglés difirió notablemente de acuerdo con los sistemas de búsqueda (p. ej.: en el caso del chino simplificado, obtuvimos 11, 148 artículos con el sistema de búsqueda local y 803 con Scopus). Google Scholar y los sistemas locales de búsqueda arrojaron la mayor cantidad de artículos en 11 y 4 idiomas diferentes al inglés, respectivamente. Sin embargo, la proporción de artículos sobre conservación revisados por pares y publicados en idiomas diferentes al inglés fue mayor en Scopus, seguida por Web of Science y los sistemas locales de búsqueda, con la menor proporción en Google Scholar. Aproximadamente el 20% de la muestra de artículos en idiomas diferentes al inglés no contaban con título o con resumen en inglés; por lo tanto, en teoría, eran imposibles de encontrar mediante palabras clave en inglés. Las posibles explicaciones de esto incluyen las barreras del idioma y la necesidad de difundir la investigación en países en los que el inglés no se habla extensamente. Con los sesgos conocidos de los métodos estadísticos y de las características de estudio entre los trabajos en inglés y en otros idiomas, los artículos en idiomas diferentes al inglés seguirán desempeñando un papel importante en el entendimiento de la biodiversidad y su conservación. Incremento de la Literatura sobre la Conservación de la Biodiversidad en Idiomas Diferentes al Inglés 摘要: 如今, 英语在科学研究中被广泛的使用, 同时英语出版物 (ELPs) 也在迅速增加。非英语科学出版物的数量通常被认为正在减少。这一假设导致非英语出版物在保护科学、实践和政策中的使用不足, 特别是在国际层面。并且, 关于以不同语言发表的保护科学的文献数量的报道也鲜有记载。因此，我们使用本土和国际搜索系统搜索并统计了1980年至2018年间以英语和15种非英语发表的关于生物多样性和保护的文献。此外, 我们还比较了不同语言文献的增长率。我们发现, 在过去39年中, 每年出版的关于保护的非英语文献中, 至少有12种语言的文献数量显著增加, 增长速度与英语文献相似。根据搜索系统的不同, 另外3种语言文献的结果却相反。保护相关的文献从20世纪80年代初开始出现, 自20世纪90年代以来, 大多数语言的保护相关的文献呈指数级增长。我们还观察到, 在搜索系统中发现的非英语文献数量存在显著差异。谷歌学术和本土文献搜索系统中共有11种和4种非英语语言的文献最多。然而, 以非英语语言发表同行评议的相关文献的比例在Scopus中最高, 其次是Web of Science和本土搜索系统, 在谷歌学术中最低。在抽样的非英语文献中, 约有20%的文献没有英文标题或摘要。因此, 理论上 无法使用英语关键词检索。造成这种情况的原因可能是因为语言障碍, 或者在英语不普及的国家是否有必要传播科学研究。鉴于英语和非英语研究在统计结果和研究特征方面存在的已知差异, 非英语文献将继续在提高我们对生物多样性和保护的理解方面发挥重要作用。 增长中的生物多样性保护的非英语文献